2021
DOI: 10.1038/s41598-021-89963-1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of tumour-associated microbiota in human hepatocellular carcinoma

Abstract: Liver cancer is the fourth leading cause of cancer-related death. Hepatocellular carcinoma (HCC) is a primary liver cancer that results from chronic hepatitis caused by multiple predisposing factors such as viral infection, alcohol consumption, and non-alcoholic fatty liver disease. Accumulating studies have indicated that dysfunction of the gut epithelial barrier and hepatic translocation of gut microbes may be implicated in the pathogenesis of HCC. However, the translocated bacteria in HCC patients remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 37 publications
(47 reference statements)
7
51
1
Order By: Relevance
“…The increase of intestinal permeability promoted the migration of bacteria and the elevation of serum lipopolysaccharide, following with an increase of inflammatory response caused by Toll-like receptor 4 (TLR4) and eventually promoting the progression of chronic liver disease and tumorigenesis (Lin et al, 1995;Dapito et al, 2012). In addition, present study has indicated a positive correlation between gut microbiota and mortality in patients with alcoholic hepatitis (Komiyama et al, 2021). All this evidence confirmed bacterial translocation is concerned with the progression of other liver diseases.…”
Section: Discussionsupporting
confidence: 76%
“…The increase of intestinal permeability promoted the migration of bacteria and the elevation of serum lipopolysaccharide, following with an increase of inflammatory response caused by Toll-like receptor 4 (TLR4) and eventually promoting the progression of chronic liver disease and tumorigenesis (Lin et al, 1995;Dapito et al, 2012). In addition, present study has indicated a positive correlation between gut microbiota and mortality in patients with alcoholic hepatitis (Komiyama et al, 2021). All this evidence confirmed bacterial translocation is concerned with the progression of other liver diseases.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, Chlamydia infection, one of the upregulated genera in the (+/+) patients ( Figure 5 d), has been associated with increased risks to develop cervical or ovarian cancer [ 67 , 68 ]. Ruminococcus_1 , another upregulated genus ( Figure 5 d), was also defined as a tumor-associated microbiota [ 69 , 70 ]. Those findings suggest possible links of altered cervical microbiome with more aggressive phenotypes in endometriosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments suggested that anti-HBV activity is based on the regulation of the immune system by intestinal bacteria [ 98 , 99 ]. Several recent studies have shown a correlation between the intestinal microbiota and chronic HBV infection without liver injury [ 99 , 100 , 101 , 102 ], as well as HBV-related cirrhosis and hepatocellular carcinoma [ 103 , 104 , 105 , 106 , 107 ].…”
Section: Hepatitis Virusmentioning
confidence: 99%